Experimental investigation of surface roughness of CT3 steel on adhesion strength of ARC spray Al -Mg alloy coating - Le Duc Thanh; Nguyen Thi Hai Van; Ha Pham Thi; Trinh Quang Hung (Tạp chí Khoa học và Công nghệ, 2023)
Thermal spray-applied AlMg alloy coatings are frequently utilized in a variety of technical applications because of great corrosion resistance, and environmental friendliness. In this work, the effect of abrasive spraying parameters on the surface roughness of CT3 steel specimens as well as the effect of the surface roughness on the adhesion strength of Al-Mg alloy spray coating were experimentally investigated. The surface roughness was assessed using a portable roughness gauge. The adhesion strength of the coating was evaluated by the pull-off test, according to the JIS H8664-1977 standard. The experimental findings indicate that air pressure and spraying distance have great impacts on the surface roughness of CT3 steel. The adhesion strength of the Al-Mg coating applied on CT3 steel is found to be almost linearly proportional to the surface roughness. The maximum adhesion strength of 14 MPa was achieved at the highest Rz of about 61 µm.